The Neglected Clubfoot (Global Journal of Medical Research, 2018)
The neglected clubfoot is an uncommon condition in the developed world that has not been clearly defined in the literature. The condition is more common in the developing nations as a result of lower detection rates early in life for various economic and cultural reasons. In addition to the physical, social and financial burden which often occurs, there is a psychological component that must be addressed prior to commencing orthopaedic management. When left untreated beyond walking age, the weight bearing on the side of the foot worsens the deformity in addition to the worsened contractures due to increased contractile elements in the soft tissues. Treatment traditionally started with casting utilising the Ponseti technique followed by extensive open surgery which may entail soft tissue procedures plus or minus bony correction. Bony procedures involving osteotomies often result in an obviously shortened foot and may be associated with skin necrosis, psuedoarthrosis, infection and vascular damage. These procedures are also not uncommonly associated with pain, weakness, and stiffness of the foot and ankle postoperatively.
Keywords: clubfoot; neglected